Challenges And Opportunities In Implementing A Knowledge Management Road-Map - Alstete, Jeffrey (Journal of Knowledge Management Practice, 2012)
This research study paper seeks to find out what strategic and operational trials organizations face when implementing a knowledge management (KM) road-map system and achievements can be accomplished. A multiple case-study approach was used to examine what currently exists in knowledge management systems implementation, how the systems compare to established knowledge management concepts, and what challenges managers are facing in improving the organization’s effectiveness. In examining a KM road-map execution in different industries, the case studies revealed that there are similarities although the tactics, tools, and techniques varied somewhat among the organizations. A common finding is that firms do have a clear idea of how knowledge management can and does benefit the organization, as well as how critically important managing knowledge assets are today. Opportunities and challenges were identified in developing consistent guidelines, willingness of employees to share knowledge, acceptance of new ideas and practices, and securing approval from top management to increase the usage of knowledge systems.